Effect of Physical Activity, Sleep Quality and Body Mass Index on Vo2max of Football Athletes Ssb Ripans Soccer School Padang - Oktavian, Ovan Elsapta; Donie, Donie; Welis, Wilda; Bahtra, Ridho; Zarya, Fiky (JETL (Journal of Education, Teaching and Learning), 2024)
This study identified low VO2 Max in SSB Ripan's Soccer School Padang football athletes, which is suspected to be due to lack of physical activity, poor sleep quality, and sub-ideal body mass index (BMI). The impact of low VO2 Max includes rapid fatigue and decreased concentration, especially in the second half of the match, which affects the team's performance. The purpose of the study was to analyze the effect of physical activity, sleep quality, and BMI on the VO2 Max of athletes. The type of research is quantitative with a comparative approach, involving 25 athletes with purposive sampling techniques. The instruments used included the IPAQ-SF questionnaire for physical activity, PSQI for sleep quality, anthropometric test for BMI, and YO-YO IR Test level 1 for VO2 Max. The data were analyzed using path analysis at α = 0.05. The results of the study showed: (1) physical activity had a direct effect on VO2 Max (py1 = 0.442), (2) sleep quality had a direct effect (py2 = 0.301), (3) BMI had a direct effect (py3 = 0.355), (4) there was an indirect effect of physical activity through BMI (total influence 0.319%), and (5) an indirect effect on sleep quality through BMI (total influence 0.323%). Overall, physical activity, sleep quality, and BMI contributed 70.1% to the athletes' VO2 Max. In conclusion, there was a significant influence of physical activity, sleep quality, and BMI on the VO2 Max of SSB Ripan's Soccer School Padang football athletes